New Normal in the Sunnah of the Prophet - Saifuddin Saifuddin; Hasanah Hasanah; Akhyar Akhyar; Syarifah Rahmiza Muzana; Ade Ulfa Syakinah; Mailina Astuti (AL-ISHLAH: Jurnal Pendidikan, 2022)
The New Normal according to Islam, returns to the life order of habluminallah, habluminannas and habluminala’lam. However, the most important thing is how the relationship between the new normal relates to humans and nature at the same time. This has been explained by the Prophet Muhammad in the hadith as applied at the time. The purpose of this study is to analyze and find the Sunnah backthat the Prophet Muhammad has applied to this fellow beings in this family, environment, friends and followers. The reseach method library research by analyzing the hadiths regarding the life of the Prophet during the pandemic.The results showed that he always applied attitudes; tawakkal to Allah SWT, be patient attitudes in dealing with disease outbreaks, Instilling an optimistic attitude and haqqulyaqin on all the provisions of Allah, endeavors in facing any situation. So thus our role in dealing with disease outbreaks during the New Normal period is to continue to refer to the hadiths that the Prophet conveyed during his lifetime to this friends